The perception of quality of service, community tourism case of the province of Chimborazo - Funes Samaniego, Liliana; Gavilánez Vega, María Isabel; Burbano Perez, Ángel Bolívar; Perez Salas, Franciso (mktDESCUBRE; Vol 1 No 19 (2022): Nineteenth Edition (January - June)DO - 10.36779/mktdescubre.v1i19.686, 2022)
The objective of this research is to analyze the perception of the quality of the services provided by one of the communities of the Corporation for the Development of Community Tourism (CORDTUCH) in this case, the study is carried out in the Royal Palace located in the rural parish from Calpi, 12 km from Riobamba capital of the Province of Chimborazo, for which a set of attributes is established to be evaluated by national and foreign tourists, its methodological application is given through descriptive, field and transversal way that was carried out between the years 2017 and 2018, in that sense it was framed through the inductive - deductive method, which allowed the assessment of the quality of the services they offer; in this sense, it is sought that the results allow a strengthening of community tourism, the generation of actions aimed at economic development, the implementation of policies that allow the consolidation of what s Services offered based on the favorable perception received of certain variables, generating new studies such as neuroeconomics.